Trinidad carnival : the cultural politics of a transnational festival - Green, Garth L.; Scher, Philip W., 1965- (Indiana University Press, 2007)
Like many Caribbean nations, Trinidad has felt the effects of globalization on its economy, politics, and expressive culture. Even Carnival, once a clandestine folk celebration, has been transformed into a major transnational festival. In Trinidad Carnival, Garth L. Green, Philip W. Scher, and an international group of scholars explore Carnival as a reflection of the nation and culture of Trinidad and Trinidadians worldwide. The nine essays cover topics such as women in Carnival, the politics and poetics.